A simple and fast sampling method for chemical analyses and densitometry of bones through rib biopsies in cattle - Malafaia, Pedro; Salcedo, Yury T.G. [UNESP]; Uscategui, Ricardo A.R. [UNESP]; Souza, Vinícius C. [UNESP]; Fleury, Diogo A. Costa; Berchielli, Telma T. [UNESP] (FapUNIFESP (SciELO), 2017)
We developed and evaluated a fast and simple method to obtain suitable bone samples for densitometry and chemical analysis through biopsies of the 12th rib of cattle. The postoperative recovery, dry matter intake (DMI) and average daily weight gain (ADG) was evaluated in 36 Nellore steers, nine of which were randomly selected for the control group and 27 others were rib biopsied. Every 30 days, rib biopsy was performed in nine steers, using a corded-electric pistol-grip drill coupled with a hole saw of a 3mm diameter pilot drill bit. This rib biopsy technique provided a suitable sample obtained in a fast way and allowed the surgeon to work alone with the animal slightly sedated and restrained in the crush. Dry matter intake (DMI) was not affected in biopsied animals. At the end of the experimental period (116 days) the average daily weight gain (ADG) was similar in the steers biopsied or not. The described method provided rib samples from cattle suitable for densitometry and chemical analysis of bone tissue without effects on health and performance. This informa tion could greatly increase the accuracy for the diagnosis of phosphorus deficiency in cattle raised on pasture and allow the evaluation of bone metabolism in experimental animals.
Keywords: Bone densitometry; Bone mineral density; Bos indicus; Cattle; Chemical analysis; Mineral deficiency; Phosphorus; Rib biopsy; Sampling method